1982
DOI: 10.1007/bf00441152
|View full text |Cite
|
Sign up to set email alerts
|

Subacute sclerosing panencephalitis in a brother and sister

Abstract: This paper describes the very rare occurrence of subacute sclerosing panencephalitis (SSPE) in two siblings: a Turkish boy and his younger sister. The clinical picture was characteristic, and the diagnosis was confirmed in both cases by appropriate laboratory examination. The interval between the occurrence of the first neurological symptoms in the boy, and subsequently in the girl was four years. Study of HLA- and 27 other polymorphic marker-systems did not reveal linkage to one of the systems tested. Therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

1984
1984
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 16 publications
0
5
1
Order By: Relevance
“…The discrepancy in evaluation of effectiveness of IFN between our case and previous cases ( 2 , 3,4), may be due to I) types of IFNs; 2) doses of injected IFNs; 3) route of administration: intramuscularly, intravenously, intraventricularly or intrathecally ; and 4) stage of the disease.…”
Section: Iycontrasting
confidence: 78%
See 1 more Smart Citation
“…The discrepancy in evaluation of effectiveness of IFN between our case and previous cases ( 2 , 3,4), may be due to I) types of IFNs; 2) doses of injected IFNs; 3) route of administration: intramuscularly, intravenously, intraventricularly or intrathecally ; and 4) stage of the disease.…”
Section: Iycontrasting
confidence: 78%
“…Another girl, aged 10, who was reported by Bartram et al and who seemed to be at the end of stage 2, was given 21 daily intraventricular injections, a total of 73x10' IU of HuIFN-/3 (human fibroblast interferon), followed by 14 daily ventricular administrations, a total of 12x 10' IU of HuIFN-a, through an Ommaya valve (3). None of the cases revealed any improvement in their clinical courses.…”
Section: Iymentioning
confidence: 94%
“…This is in spite of the observations that IFN may be involved in the establishment of persistent infections by measles virus in vitro (24,43) and that it can serve as a marker for persistent CNS infection by canine distemper virus in dogs (49). Furthermore, in trials of intrathecal or intraventricular IFN as a treatment for SSPE (6,7,9,22,(39)(40)(41)(42)47), clinical improvement has been observed in 9 of 19 (47%) patients, which is in contrast with the approximately 10% of patients with SSPE that show spontaneous stabilization or improvement (44,45). Furthermore, by combining the results reported with some of these trials with those reported in other studies (6,7,9,22,29), it can be seen that of 20 patients with SSPE whose cerebrospinal fluid was assayed for IFN by bioassay before treatment with IFN, only 4 (20%) had detectable levels.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we expected the effect of IFN, which not only has antiviral properties but also modifies the immune response and activates natural killer cells. Up to the present, there have been only a few papers concerning the effects of IFN on SSPE (Behan 1981;Bartram et al 1982). But the decision on the effects of IFN treatment must be made carefully, in view of reported occurences of spontaneous long-term improvement or remission (Risk and Haddad 1979).…”
Section: Resultsmentioning
confidence: 99%